Value Congruence and Charismatic Leadership in CEO–Top Manager Relationships: An Empirical Investigation - Hayibor, Sefa; Agle, Bradley R.; Sears, Greg J.; Sonnenfeld, Jeffrey A. 1954-; Ward, Andrew (2011)
Although charismatic leadership theorists have long argued that leader–follower value congruence plays a central role in the development of charismatic relationships, few studies have tested this proposition. Using data from two studies involving a total of 329 CEOs and 1807 members of their top management teams, we tested the hypothesis that value congruence between leaders and their followers is empirically linked to follower perceptions of the charisma of their leader. Consistent with a relational perspective on charismatic leadership, strong support was found for the hypothesis that perceived value congruence between leaders (CEOs) and their followers (members of their top management teams) is positively related to follower perceptions of the degree of charisma possessed by the leader. Conversely, only limited support was found for the hypothesis that actual value congruence is linked to perceptions of charismatic leadership. Implications of these findings for research and practice are discussed.
Keywords: Values; Value congruence; Top management; Leadership; Charisma